KAJIAN SEMIOTIKA PADA IKLAN TELEVISI OLX.CO.ID “BEKAS JADI BERKAH” - Bobby Halim (UNIVERSITAS INDO GLOBAL MANDIRI, 2017)
The purpose of this research is to know the semiotics of an OLX commercial named with “Former became Blessing”. It examined the relationship of laying camera angle in influencing message delivered by a TVC and how the cinematography is used as a visual rhetoric. The study was conducted qualitatively by semiotic analysis approach to the film. Itanalyzed by using a diachronic view of signifier and the signified. This study reveals the meanings contained in the TVC OLX.co.id “Former became Blessing”. By using one of the theories of Ferdinand de Saussure, TVC is the subject of the study authors described a scene. Presented through tables and also in the form of a paragraph so that the reader can follow the process of analysis that has been done by researchers. Keywords : commercial, semiotics, film, cinematography